The policy implementation gap of school oral health programmes in Tshwane, South Africa: a qualitative case study - Mpho Molete; Aimee Stewart; Edna Bosire; Jude Igumbor (BMC, 2020)
Abstract Background School going children across the world continue to experience high levels of untreated dental diseases. The South African Oral Health policy documents present measures to address the oral health needs of children in school settings, yet the burden of oral disease in the country is over 50% among primary school children. Methods Our study therefore sought to assess the implementation of school oral health programmes in Tshwane in line with policy recommendations using the Walt & Gilson policy analysis triangle. A qualitative explanatory case study was undertaken using a combination of data from direct observations and interviews. The case analysis involved assessing the processes of providing school oral health programmes that were offered at 10 schools in Tshwane. The measuring tools included process maps and an interview guide. Results The results found that policy implementation was affected by poor prior planning, inadequate resources, poor school infrastructure and lack of support from key stakeholders. Furthermore, inconsistencies in policy interpretation by management, coupled with the fact that the oral hygienists were not conversant with the policy hampered delivery of the policy content. The variations in policy implementation observed were often at the discretion of the oral hygienist in response to contextual challenges. Conclusion There was policy and practice misalignment and variations in the processes of implementing oral health programmes across the 10 schools. Hence regular monitoring, evaluation and root cause analysis is recommended for such programmes in order to make informed decisions on contextually relevant and standardised programme modifications.